Kerajaan Seribu Tahun - Samuel Bartolo; Aprianus Moimau (International Forum of Researchers and Lecturers, 2024)
The Millennium or Millennium in a Biblical perspective is the period of Christ's reign on earth referred to in the book of Revelation. This article will discuss in depth the Biblical view of the Millennial Kingdom, including theological interpretation, implications for Christians, and relevance in the context of eschatology. Through analysis of Biblical texts, especially the book of Revelation, this article seeks to provide a comprehensive understanding of this concept.